Management of Midline Diastema Using Removable Orthodontic Appliances Combined with Frenec-tomy: A Case Report - Irfan Maulana Aji Setiawan; Regina Meilin Syahputri; Reni Kurniasari (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: A midline diastema is a gap between the maxillary central incisors that can lead to aesthetic, psychological, and social issues. Its etiology is multifactorial, with one contributing factor being a high-attachment superior labial frenulum, which may cause relapse following orthodontic treatment. Case: A 22-year-old female patient presented with the chief complaint of a 1.5 mm gap between her upper front teeth, which significantly disturbed her appearance. The patient also had a habit of biting pencils and a history of relapses after previous orthodontic treatment. Case Management: The patient was treated with removable orthodontic appliances consisting of active maxillary and mandibular plates. The active components included finger springs, a labial arch, and continuous springs, which were gradually activated during each follow-up visit. At the eighth follow-up visit, a frenectomy was performed at the Department of Periodontics due to the high attachment of the superior labial frenulum, which posed a potential risk for relapse. Removable orthodontic appliances have been reported to be effective in closing mild to moderate midline diastema, particularly through the tipping movement of anterior teeth. Patient compliance, controlled activation, and appropriate appliance design are critical determinants of success. Frenectomy also contributes to the stability of the outcome by eliminating soft tissue tension that could potentially reopen the diastema gap. Conclusion: The combination of removable orthodontic treatment, frenectomy, and a retention phase with a retainer can yield optimal results in midline diastema cases. Comprehensive evaluation of etiological factors, patient adherence, and long-term monitoring are strongly recommended to prevent relapses.